Aerobic exercise improves hippocampal blood flow for hypertensive Apolipoprotein E4 carriers. Issue 8 (August 2021) - Kaufman, Carolyn S; Honea, Robyn A; Pleen, Joseph; Lepping, Rebecca J; Watts, Amber; Morris, Jill K; Billinger, Sandra A; Burns, Jeffrey M; Vidoni, Eric D
Cerebrovascular dysfunction likely contributes causally to Alzheimer's disease (AD). The strongest genetic risk factor for late-onset AD, Apolipoprotein E4 ( APOE4 ), may act synergistically with vascular risk to cause dementia. Therefore, interventions that improve vascular health, such as exercise, may be particularly beneficial for APOE4 carriers. We assigned cognitively normal adults (65–87 years) to an aerobic exercise intervention or education only. Arterial spin labeling MRI measured hippocampal blood flow (HBF) before and after the 52-week intervention. We selected participants with hypertension at enrollment (n = 44). For APOE4 carriers, change in HBF (ΔHBF) was significantly ( p = 0.006) higher for participants in the exercise intervention (4.09 mL/100g/min) than the control group (−2.08 mL/100g/min). There was no difference in ΔHBF between the control (−0.32 mL/100g/min) and exercise (−0.54 mL/100g/min) groups for non-carriers (p = 0.918). Additionally, a multiple regression showed an interaction between change in systolic blood pressure (ΔSBP) and APOE4 carrier status on ΔHBF ( p = 0.035), with reductions in SBP increasing HBF for APOE4 carriers only. Aerobic exercise improved HBF for hypertensive APOE4 carriers only. Additionally, only APOE4 carriers exhibited an inverse relationship between ΔSBP and ΔHBF. This suggests exercise interventions, particularly those that lower SBP, may be beneficial for individuals at highest genetic risk of AD. ClinicalTrials.gov Identifier : NCT02000583